(untitled) (The Research of Medical Science Review, 2025)
About one-third of patients with post-stroke reported with dysphagia. Post-stroke dysphagia is a quotidian cause of increased holocaust and hospitalization; this may mar quality of life, rate of mortality. Post stroke dysphagia has been cognate with aspiration pneumonia and mortality. PSD management is challenging and necessitates a multidisciplinary approach. Although some people respond well to conventional treatments like speech therapy, oral hygiene and medication; they may not be procurable or available to everyone. On the other hand, an optimistic non-pharmacological intervention for the management of PSD is physical exercise. Physical exercise has emerged as viable additional or simulated treatment for PSD control. There is mounting evidence that suggests physical activity can improve swallowing along with speech. Studies have shown that physical therapy interventions, such as oral neuromuscular training, resistance exercises for muscles of mastication, intraoral myofascial therapy, intraoral electrical stimulation, etc. can help stroke survivors with PSD who struggle with dysphagia as well as their quality of life. Additionally exercise has been linked to improvement in brain functions. This review intends to look at the evidence of Oral neuromuscular training in treating PSD, considerable beneficial effects and its etiology. For this review articles have been selected by using databases like Google scholar, Pedro, PubMed according the inclusion and exclusion criteria. Studies included are randomized controlled trials.